2016
DOI: 10.1039/c6fo00041j
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid attenuated apoptotic and inflammatory stress in the striatum of MPTP-treated mice

Abstract: The effects of post-treatments with asiatic acid (AA) at 20, 40 or 80 mg per kg BW per day against apoptotic, oxidative and inflammatory injury in the striatum of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated mice were examined. The results showed that AA supplements at 40 and 80 mg per kg BW per day increased AA deposit in the striatum, increased glutathione content and decreased reactive oxygen species production in the striatum. AA supplements at 20-80 mg per kg BW per day dose-dependently low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Antioxidant and antiapoptotic effects were also involved in the therapeutic potential of asiatic acid in PD. These effects were observed in rotenone-induced apoptosis in SH-SYS5Y cells [115,116] and further confirmed in MPTP-treated mice, as an in vivo model of PD [117]. After oral administration of asiatic acid, an increase in striatal glutathione levels, decrease in ROS production, and modulation of the apoptotic process, together with anti-inflammatory effects, were observed.…”
Section: Asiatic Acidsupporting
confidence: 54%
See 2 more Smart Citations
“…Antioxidant and antiapoptotic effects were also involved in the therapeutic potential of asiatic acid in PD. These effects were observed in rotenone-induced apoptosis in SH-SYS5Y cells [115,116] and further confirmed in MPTP-treated mice, as an in vivo model of PD [117]. After oral administration of asiatic acid, an increase in striatal glutathione levels, decrease in ROS production, and modulation of the apoptotic process, together with anti-inflammatory effects, were observed.…”
Section: Asiatic Acidsupporting
confidence: 54%
“…After oral administration of asiatic acid, an increase in striatal glutathione levels, decrease in ROS production, and modulation of the apoptotic process, together with anti-inflammatory effects, were observed. These effects could be explained by the suppression in the striatal expression of toll-like receptors (TLRs) and NF-κB [117]. Asiatic acid also improved dopamine striatal levels, thus ameliorating dopaminergic neurodegeneration, along with a marked neurotrophic effect by increasing the neurotrophins BDNF and glial cell line-derived GDNF [117] and its tyrosine kinase receptors (TrKB) [118].…”
Section: Asiatic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Nataraj et al ( 2017 ) demonstrated the antioxidant, cytoprotective and antiapoptotic activities of AA against rotenone-induced cytotoxicity in SH-SY5Y cells. The in vitro results were further confirmed in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson's disease in mice (Chao et al, 2016 ). AA found bioavailable in the striatum and reduced free radical generation along with raised glutathione levels.…”
Section: Asiatic Acid In Parkinson's Diseasementioning
confidence: 85%
“…AA was well-tolerated up to a dose of 75 mg/kg (Lee et al, 2012 ). The bioavailability of AA in the plasma, brain, heart, liver, kidney, colon and bladder is more when fed with AA containing fruits and vegetables for several weeks (Yin et al, 2012 ; Chao et al, 2016 ).…”
Section: Pharmacokinetic Properties Of Asiatic Acidmentioning
confidence: 99%